PENGARUH IMPLEMENTASI BUDAYA KERJA (CATATAN LAPORAN CAPAIAN KINERJA HARIAN) TERHADAP PENINGKATAN KINERJA PEGAWAI PADA IAIN BENGKULU - Khairiah Khairiah (Universitas Islam Negeri Fatmawati Sukarno, 2016)
The purpose of this research was to describe the influence of work culture (note on report of daily performance achievements) toward employees’ performance at IAIN Bengkulu. This research used survey methods and technical of path analysis through SPSS. The samples in this study were 24 employees in IAIN Bengkulu. The samples were taken using proportional random sampling technique. The results showed that there is a direct effect of the positive and significant correlation between workplace cultures (note on report of daily performance achievements) on employees’ performance in IAIN Bengkulu. Based on these results, the researcher suggests the need to maintain the employees’ performance in IAIN Bengkulu in the future the need to maintain and enhance the cultural quality of work through the budget provision or application toward note on report of daily performance achievements through online. To the leader as the direct supervisor is expected to constantly monitor, evaluate and know by affixing a signature every day to his each subordinates then note on report of daily performance achievements of employees there is conformity duties between SKP (target of employees’ performance) / labor contract in the earlier year with a record that is done every day by employees. The employees of IAIN Bengkulu are expected to always make the note on report of daily performance achievements every day in accordance with their duties and functions as well as responsibilities in the work